How can extensive grazing be beneficial for the restoration of dryland ecosystems? - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2022)
Presentation on knowledge on the beneficial role of extensive grazing for the restoration of dryland ecosystems. The presentation was performed by Dr. Mounir Louhaich during the FAO-GLF Digital Forum. The digital forum is hosted jointly by the Global Landscapes Forum and the Food and Agriculture Organization of the United Nations (FAO).